The effect of foot reflexology on duration of labor and neonatal Apgar score in nulliparous women: a randomized clinical trial - Mahboubeh Valiani; Maryam Kianpour; Elaheh Shiran (Mashhad University of Medical Sciences, 2022)
Introduction: One of the risk factors for low Apgar score at birth is duration of labor and its increase. Todays, various pharmachological and non-pharmachological methods are used to reduce labor pain and also the duration of labor. One of these effective methods is reflexology (hand message on feet) during labor which reduces labor pain. Therefore, this study was performed with aim to evaluate the effectiveness of this method on duration of labor and neonatal Apgar score and compare it with the routine care of hospital. Methods: This quasi-experimental randomized controlled clinical trial study was performed in 2009-2010 on 88 pregnant women referred to Shahid Beheshti and Asgariyeh hospitals in Isfahan for vaginal delivery. The subjects were randomly divided into two groups of intervention (reflexology) and control (routine care). Data collection tool was a questionnaire consisting of two parts of personal characteristics (age, place of residence, occupation, education level) and gestational age and the second part was related to duration of labor and delivery outcome (first and fifth minute Apgar score). Data were analyzed by SPSS software (version 18) and Chi-square and variance analysis tests. P<0.05 was considered statistically significant. Results: Mean first and fifth minutes Apgar scores after birth was not statistically significant between the two groups (P<0.001). The length of active phase of labor was significantly different between the two groups. In the reflexology group, the length of active phase of labor was shorter than this time in routine care group, but this difference was not significant during the second (p=0.29) and third stages (p=0.27) Conclusion: Foot reflexology directly reduce the labor duration and labor pain which is effective in contribute to shorten the prevalence of asphyxia and improving the Apgar score.